Analisis Kinerja Keuangan pada Perusahaan Manufaktur Sub Sektor Tekstil dan Garment yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2020-2023 - Jaeng, Theresa Yuliana; Tunya, Maria Grasella; Gula, Valeria Eldyn (PUTRA JAWA PUBLISHER, 2025)
The aim of this research was to evaluate the financial performance of manufacturing companies in the textile and garment sector that are listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023 by analyzing various financial ratios such as liquidity, solvency, profitability, and activity. The study utilized secondary data and employed a quantitative research approach, focusing on 18 companies as the subjects. Data was collected through documentation methods. The findings revealed that only PT. Tifico Fiber Indonesia Tbk consistently maintained a high liquidity ratio each year, indicating a strong financial position. Both PT Buana Artha Anugerah Tbk and PT. Tifico Fiber Indonesia Tbk were noted to be solvent companies as they maintained low debt ratios throughout the years. Additionally, PT. Panasia Indo Resources Tbk demonstrated impressive profitability over the past three years. Uni-Charm Indonesia Tbk and PT Pan Brothers Tbk also performed well in terms of activity ratios, surpassing industry benchmarks.